Ian Gordon. Kid Comic Strips: A Genre Across Four Countries. New York: Palgrave Macmillan, 2017. ---. Superman: The Persistence of an American Icon. New Jersey: Rutgers UP, 2017. - Cathy L Ryan (Studies in 20th & 21st Century Literature, 2017)
Review of Ian Gordon. Kid Comic Strips: A Genre Across Four Countries. Palgrave Studies in Comics and Graphic Novels, Ed. Roger Saban. New York: Palgrave Macmillan, 2017. Review of Ian Gordon. Superman: The Persistence of an American Icon. New Jersey: Rutgers UP, 2017.
Keywords: comics; children’s comics; kid comic strips; Comics Studies; Ian Gordon; Superman